Radiosurgery: Teenage Sex or Midlife Crisis? - Tripathi, Manjul (Frontiers in Surgery, 2022)
For a beginner, radiosurgery seems as fascinating as teenage sex. It has all the ingredients of adolescent attraction. An early career neurosurgeon feels pretty excited and loves to try it. Looking at the limited radio surgical centers in teaching institutes, radiosurgery appears to be a mystical and novel first experience with the radiation tool in the realm of a neurosurgeon. However, without proper guidance, the initial attempts do not feel that enjoyable as there is no immediate result, no blood bath, and the surgeon needs to wait for a longer time for the lesion to disappear or primarily reduce by some quarters at its best. Until you understand the philosophy of radiosurgery, you are bombarded with conflicting messages from traditional neurosurgical practitioners and competing radiation oncologists. As you no more battle with blood and flesh, you remain concerned about what peers think about you. Neurosurgeons interested in radiosurgery feel threatened to be labelled 'chicken hearted' or non-operative neurosurgeons; however, once you understand it and learn the science and craft of radiosurgery, you want to perform much better every time you do it. On the other hand, SRS proved to be a distracting force for some seasoned neurosurgeons. SRS especially made a paradigm shift in managing two intracranial disorders; vestibular schwannoma and arteriovenous malformation(3, 4). It is not uncommon to hear a debate in current neurosurgical conferences on micro neurosurgery versus radiosurgery for many intracranial diseases. This changed the surgical practice of many traditional skull base and vascular neurosurgeons. With this sweeping change, a hostile environment emerged, mainly because of neurosurgeons trained before the popularity of radiosurgery. They perceived the gamma knife as a threat to the surgical knife and an unwanted encroachment in their field. With growing literature supporting the effectiveness of this new blade, a state of midlife crisis has started to settle in the neurosurgical mindset, where the surgeon is married to the operating room but is having an affair with the radiosurgery station.